Upaya Guru Pendidikan Agama Islam Mengembangkan Karakter Religius Peserta Didik SDIT Imam Asy-Syafii Pekanbaru - Nurhaibi, Nurhaibi; Zalisman, Zalisman; Hariati, Haryuni (Mitra PGMI: Jurnal Kependidikan MI, 2023)
This study aims to explore the professionalism of PAI teachers in developing the religious character of students. The research method used was qualitative with a case study approach, by interviewing seven research informants, namely the school principal and six PAI teachers. Data were analyzed using data reduction, data presentation, and conclusions and verification. The results showed that the efforts made by PAI teachers at SDIT Imam Asy-Syafii Pekanbaru in developing the religious character of students were done in a systematic way. Furthermore, in the teaching and learning process, learning materials are again inserted which emphasize the values of religious character in students. The supporting factor is that in the school environment there is a mosque that is quite large with complete facilities so that some student activities can be carried out in the mosque including sunnah dhuha prayers, noon and asr prayers, most of the students' guardians also understand the sunnah and one manhaj with the school so that the education received students at school are the same color as the education they receive at home. The inhibiting factor is that there are still guardians of students who are not yet semanhaj and the pattern of education at home and at school for children is different. The findings in this study have implications for the professional theory of Islamic religious education teachers in building students' religious character.